O Ecossistema de Startups de Software de Belo Horizonte e sua maturidade - de Almeida, Pedro Augusto Duarte; de Almeida, Sandro Jerônimo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Startups ecosystems have emerged in different parts of the world, contributing to the socioeconomic development of society. In Brazil, the growth of ecosystems with public and private actions has been observed, mainly in large capitals, but it is not always clear how these ecosystems are evolving and what actions would be most adequate for their growth. Understanding the maturity of an ecosystem is important for a correct direction of actions and resources that favor an evolution of its local economy. This work carried out a maturity evaluation in the Belo Horizonte's Startups Ecosystem, one of the largest in Brazil and Latin America. Using a qualitative and quantitative methodology and interviews with the main actors of the ecosystem, areas that are essential for the economic and socio-cultural growth of the region, such as technological, educational aspects, characteristics of entrepreneurs and investors were addressed. As a final result, information was obtained that provided a better understanding of the evolution of the innovation ecosystem of Minas Gerais capital and its future perspectives, with a major focus on Software Startups.